2019
DOI: 10.1021/acs.analchem.9b02613
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Observation of Photoswitching by NMR Spectroscopy: A Photochemical Analogue to the Exchange Spectroscopy Experiment

Abstract: We present 1D and 2D NMR experiments that provide in situ insights into photoinduced isomerizations. Irradiation during the mixing period of an exchange spectroscopy (EXSY) experiment leads to characteristic cross peaks in 2D spectra. The phototriggered exchange of magnetization occurring in photoswitchable (Z)-and (E)isomers of three selected azo compounds provides information on the dynamic E/Z equilibria. We report the dependence of the diagonal-to-cross-peak ratio on concentration, light intensity, and mix… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 55 publications
0
14
0
Order By: Relevance
“…For photo-CIDNP studies, we found LED pulse width modulation (PWM) control directly by the NMR console to be particularly useful and convenient, and it removes the need for additional PWM light dimming electronic components as used elsewhere. 41 The multiple channel/LED aspect of the NMRtorch approach is also particularly advantageous for studies of photoswitches. For example, although photoisomerisation of azobenzene-based dyes has previously been studied by NMR spectroscopy using both in [38][39][40][41] and ex situ 43 illumination, rapid multicolour switching of LED illumination demonstrated here enables additional kinetic and equilibria processes to be easily observed at a number of wavelengths, reducing the dead time of the experiments, and allowing to characterise fully the behaviour of a photoswitch in response to a range of stimuli (Figure 5).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For photo-CIDNP studies, we found LED pulse width modulation (PWM) control directly by the NMR console to be particularly useful and convenient, and it removes the need for additional PWM light dimming electronic components as used elsewhere. 41 The multiple channel/LED aspect of the NMRtorch approach is also particularly advantageous for studies of photoswitches. For example, although photoisomerisation of azobenzene-based dyes has previously been studied by NMR spectroscopy using both in [38][39][40][41] and ex situ 43 illumination, rapid multicolour switching of LED illumination demonstrated here enables additional kinetic and equilibria processes to be easily observed at a number of wavelengths, reducing the dead time of the experiments, and allowing to characterise fully the behaviour of a photoswitch in response to a range of stimuli (Figure 5).…”
Section: Discussionmentioning
confidence: 99%
“…The trans-cis isomerisation of azobenzene and its derivatives is one such light induced transition, which may serve as a useful photoswitch in biotechnology applications. 37 Although some transitions in such system have been characterised by NMR before with in situ illumination, [38][39][40][41] , exploring transitions triggered by toggling between numerous illumination colours would be more informative. To illustrate the application of the NMRtorch approach to characterise the kinetics of photoswitches, the photoisomerisation of 1 mM 4aminoazobenzene (AAB) in DMSO-d6 was studied under continuous illumination with a variety of light wavelengths (Figure 5).…”
Section: Studying Multi-colour Triggering Of Photoswitchesmentioning
confidence: 99%
“…Molecular spin switches operated with visible light in homogeneous solution [ 1 ] or on surfaces [ 2 ], hold promise for a number of hitherto unprecedented applications such as switchable contrast agents [ 3 – 7 ], switchable NMR relaxation agents [ 8 – 10 ], and building blocks for molecular spintroncis [ 11 ]. Our modular design is based on three components: a) a Ni(II)-porphyrin (square planar base complex), b) an azoaryl unit (photoswitchable ligand) and c) a molecular linker or tether (connecting the porphyrin with the switchable ligand).…”
Section: Introductionmentioning
confidence: 99%
“…A review of modern NMR methods for studying the kinetics of reversible and irreversible processes is given in. [8,9,[19][20][21] In particular, the technique (named the homonuclear doubleresonance transfer of local nuclear spin population inversion) was proposed for a qualitative and quantitative study of the kinetics of reversible and irreversible processes. [22] Although these studies have been published in specialized literature.…”
Section: Introductionmentioning
confidence: 99%